Method of Formation of Tracheo-Tracheal Anastomosis with a Continuous Single-Row Suture in the Experiment - E. O. Inozemtsev; I. S. Kurganskiy; S. A. Lepekhova; O. A. Goldberg; E. G. Grigoriev (Acta Biomedica Scientifica, 2019)
The work is devoted toanew suture in the formation of tracheo-tracheal anastomosis. Despite the improvement of surgical technique in tracheal interventions, the number of postoperative complications (insufficiency and stenosis of anastomosis) remains high, with postoperative lethality reaching 18.2 %. The main problem is the lack of a unified point of view on the choice of the method of anastomosis, in particular, inclusion in the mucosal suture. Several variants of tracheo-tracheal anastomosis are suggested, but a large number of complications testify to the shortcomings of the methods used.The aim of this work is to optimize the imposition of a continuous single-row suture for the formation of tracheo-tracheal anastomosis with a shortening of the trachea.Materials and methods. The study was carried out on the basis of the scientific department of experimental surgery with the vivarium of Irkutsk Scientific Centre of Surgery and Traumatology using Wistar rats, and approved by the ethical committee.Results. A technique for the formation of tracheo-tracheal anastomosis with the use of an original continuous singlerow suture with a shortening of the trachea was developed. Step by step a sequence of operations from access to the cervical trachea to the formation of an anastomosis.Conclusion. The discussed version of the seam in the formation of tracheo-tracheal anastomosis makes it possible to accurately compare and reliably stabilize the sewn ends of the trachea.